Exploring the Traditional Architecture of Kampung Naga: Heritage Values, Local Identity, and Sustainability - Pratama, Mochammad Gibbran Genta; Dini, Rahma Diva Januar; Sulistiani, Rina; Febriani, Feni; Sudarto, Sudarto (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2025)
The study explores the uniqueness of Kampung Naga’s traditional architecture, which is rich in noble values and local Sundanese philosophy. This study focuses on is how the architectural design incorporates the concepts of cultural preservation and environmental sustainability, which are examined through a Sundanese architectural approach. Using qualitative methods, this research investigates traditional design elements that play a role in preserving local identity while maintaining harmony between humans and nature. The results of the research show that the structure of houses in Kampung Naga not only has a physical function but also contains philosophical meanings related to beliefs and social life. The architectural design not only reflects local wisdom in the form of environmentally friendly stilt houses but also contains philosophical values that support cultural and ecological sustainability. Noble values such as simplicity and sustainability are reflected in construction patterns consistent with traditional principles. This study is expected to contribute to efforts to preserve traditional architecture while inspiring the application of local wisdom in the development of sustainable modern architecture, and providing sustainable solutions in the context of current and future development. This research serves as a bridge between cultural heritage and modern concepts of sustainability and authentic local identity.